2017
DOI: 10.1587/transinf.2016edl8248
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Human Stress Using Commercially Available Single Channel EEG Headset

Abstract: SUMMARYA study on quantification of human stress using low beta waves of electroencephalography (EEG) is presented. For the very first time the importance of low beta waves as a feature for quantification of human stress is highlighted. In this study, there were twenty-eight participants who filled the Perceived Stress Scale (PSS) questionnaire and recorded their EEG in closed eye condition by using a commercially available single channel EEG headset placed at frontal site. On the regression analysis of beta w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Electrophysiological measurements have been used to examine the players' response to games [14,15]. EEG has also been used to measure the cognitive state of the brain such as stress [16]. In [17], field experts discussed the methodological advancements within player experience and playability research considering EEG as a good measure for cognitive processing.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological measurements have been used to examine the players' response to games [14,15]. EEG has also been used to measure the cognitive state of the brain such as stress [16]. In [17], field experts discussed the methodological advancements within player experience and playability research considering EEG as a good measure for cognitive processing.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, classification accuracy is improved by 7.1% as compared to the study [24], in which low beta is used as a sole feature for classification. F-measure of proposed features is equal to that of low beta-based classification.…”
Section: Discussionmentioning
confidence: 79%
“…Table 2 compares the performance of the algorithms used in single channel-based studies for classification of human stress in terms of various performance measures. The execution times for [23, 24] and the proposed methodology are computed on an Intel i5 system with RAM of 4 GB. It is observed that the SVM algorithm, when used with the proposed features selected by CFS, gives 7.1% higher accuracy as compared to the case, where all neural oscillations are used as features.…”
Section: Discussionmentioning
confidence: 99%
“…The frontal theta activity was shown to decrease due to a stressful mental arithmetic task [32]. In [33], low beta waves in closed eye condition were found to be a strong predictor of perceived stress, where PSS score was predicted by using multiple linear regression. The pre-frontal relative gamma power i.e., the ratio of gamma band and slow brain rhythms, was proposed as a bio marker for identification of stress [34,35].…”
Section: Related Workmentioning
confidence: 94%
“…This also helped in minimizing the muscular motion and reduce these artifacts, since we recorded data at the frontal electrodes. A closed-eye condition was used, since correlates of long-term stress have been found in this condition in previous studies [10,33]. Another advantage of using the closed eye condition is the minimization of eye blink artifact.…”
Section: Data Acquisitionmentioning
confidence: 99%